2015
DOI: 10.14737/journal.aavs/2016/4.2.66.70
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Tannin Contents in Selected Agro-Industrial By-products and their Biological Activity in Precipitating Protein

Abstract: | Agro-industrial by-products containing tannins have potential to be used as alternative ruminant feed sources. To explore the functional effects of agro-industrial by-products on livestock production, the contents of tannins such as total extractable phenolics (TEPH) and condensed tannins (CT), in 15 kinds of by-products were determined and their protein-precipitating capacity (PPC) was also measured. TEPH content was the highest in chestnut husk, followed by tea grounds. Grape skin, winery residue and chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The extractable phenolic compounds were marginally higher in PS than in GP, whereas CT levels were similar between the two FBs (Supplementary Table S3). This suggested that phenolic compounds other than CT, such as hydrolyzable tannin, were higher in PS than in GP, consistent with the findings of a previous study [23]. Antimethanogenic activities of tannins have been extensively revealed in several in vitro and in vivo studies [24,25], although not completely.…”
Section: Resultssupporting
confidence: 86%
“…The extractable phenolic compounds were marginally higher in PS than in GP, whereas CT levels were similar between the two FBs (Supplementary Table S3). This suggested that phenolic compounds other than CT, such as hydrolyzable tannin, were higher in PS than in GP, consistent with the findings of a previous study [23]. Antimethanogenic activities of tannins have been extensively revealed in several in vitro and in vivo studies [24,25], although not completely.…”
Section: Resultssupporting
confidence: 86%
“…Siever had the highest tannin content because of the abundance of phenolic content in the guava peels (Jiménez‐Escrig et al., ). High concentrations of tannins in feed reduce voluntary feed intake and nutrient digestibility, whereas low to moderate concentrations might improve the digestive utilization of protein (Kondo, Jayanegara, Uyeno, & Matsui, ). The phytate content was found to be highest (0.56%) in the refiner compared with both siever (0.18%) and decanter (0.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Currently there is considerable research interest in the tannins and the benefits of agro-industrial by-products containing tannins (for example, chestnut husk, grape skin, winery residue) introduced into the diet of ruminants (Kondo et al ., 2016). Tannins are part of the group of phenolic compounds and because of their multiple phenolic hydroxyl groups, one of their main properties is the ability to form complexes with proteins.…”
Section: Introductionmentioning
confidence: 99%